Penerapan Model Pembelajaran Inkuiri untuk Meningkatkan Hasil Belajar IPA Siswa Kelas V Sekolah Dasar - Komedien, Brianne E. Jo. (Peneliti.net, 2023)
The aim of this research is to improve class V science learning outcomes at SDN Inpres 6/84 Walenekoko in the application of the inquiry model. This research uses a Classroom Action Research design which consists of planning, action, observation and reflection and is carried out in two cycles. The research data consists of information about the process and data from observations as well as a collection of each test carried out at the end of each cycle. The research subjects were 9 class V students, consisting of 3 girls and 6 boys. Carrying out this research from two cycles carried out in learning using the application of the inquiry model in class V at SDN INPRES 6/84 Walenekoko, it turned out that student learning outcomes showed a significant increase. In the implementation of cycle I, student learning outcomes averaged 71.1% and implementation of cycle II increased to 88.8%. So, the conclusion is that using the inquiry model can improve science learning outcomes for fifth grade students at SDN Inpres 6/84 Walenekoko.